Parasite detection in sand from bays on the north coast of São Paulo state, Brazil - Lucas Pires Ramos, Eliezer; Gomez-Hernandez, Cesar; Gonçalves Queiroz, Lucas; Gregorio Franco Moura, Renata; Pires Nogueira, Nathalia; Licia Santos Ferreira, Gabriela; Rezende-Oliveira, Karine (Revista de patologia tropical, 2020)
Soil contamination by protozoan parasites and soil-transmitted helminths (STH) is common in beach sand due to a number of factors such as pets, pluvial water, garbage, etc. These pathogens may cause many diseases in humans and animals and become a public health problem. Thus, systematic evaluation and inspection are necessary to develop control strategies regarding public contamination. For this purpose, our aims were to evaluate the parasitic profile of sandy soils on an urban beach and an untouched beach and correlate this with environmental and seasonal characteristics in Ubatuba, Brazil, in two seasons (winter and summer). 132 soilsamples were collected for parasite analysis utilizing Rugai’s method and the sedimentation adapted method. Our results showed positivity in 62% of the samples for at least one parasite in the urban beach and no parasitic structures on the untouched beach. The positivity was higher in summer (85%) than in winter (51.7%). All samples were positive for both, helminths and protozoa. Seasonal influence was noted regarding the presence of STH while for protozoa this influence was not observed. The parasitic structures most found were larvae of hookworms (35%) and Toxocara eggs (31.7%). We also noted the presence of Strongyloides sp, Ascarislumbricoides, coccidia, Dipylidium caninum, Entamoeba hystolitica/dispar, Endolimax nana, Entamoeba coli, Giardia sp, Toxascaris leonina, Trichuris sp and Dibothricephalus latus. There was a positive correlation between temperature and the presence of STH in the sand samples. Most of the collection sites on the urban beach presented dogs or canine traces and garbage in both seasons. There was an association between the presence of dogs or their traces and parasitic structures. In conclusion, seasonality, urbanization and the presence of pets on beaches can potentially favor environmental contamination by parasites increasing the risk oftransmission of zoonotic and parasitic diseases.KEY WORDS: Soil-transmitted helminths; protozoa; environmental contamination; sand; beaches.